Virulence factor genotyping of Helicobacter pylori isolated from Costa Rican dyspeptic patients - Molina Castro, Silvia Elena (2019)
Background and aims: Costa Rica is one of the countries with the highest incidence and mortality rates for gastric cancer. Helicobacter pylori infection rates are high in the whole country. We have previously shown that H. pylori CagA+ is significantly associated with atrophic gastritis (AG) of the antrum in a dyspeptic population. The aim of this work is to determine if other H. pylori virulence factors (vacA, dupA, oipA, iceA and babA2) are associated with atrophic gastritis (AG) or duodenal ulcer (DU). Methods: The presence of virulence genes in Costa Rican H. pylori isolates was analyzed by PCR in 151 cultured strains from patients with dyspeptic symptoms. Endoscopic and histopathological diagnoses were available. Odds-ratio and 95% confidence intervals for AG patients vs. non-atrophic gastritis (NAG) or DU patients vs. no duodenal ulcer (NDU) patients were calculated. Results: Amongst the studied isolates, 82% had the cagA+, 76.2% had the vacA s1m1, 97.0% had the oipA+, 21.0% had the icea1, 79.0% had the iceA2, 44.0% had the babA2+ and 76.0% the dupA+ genotypes. Infection with H pylori cagA+, dupA+, oipA+, iceA, babA2+, and vacA s1m1 genotypes was not associated with AG risk. The frequency of the dupA gene was 78.7 and 60.9% in isolates from patients with NDU and DU, respectively, and its presence was significantly associated with decreased risk of duodenal ulcer [odds-ratio: 0.33, p = 0.024, confidence interval 95% (0.11–0.85)]. Conclusion: H. pylori dupA genotype is inversely associated with DU risk in this population.